2017
DOI: 10.3866/pku.whxb201703292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CeO<sub>2</sub> Addition on Improved NO Oxidation Activities of Pt/SiO<sub>2</sub>-Al<sub>2</sub>O<sub>3</sub> Diesel Oxidation Catalysts

Abstract: The catalytic activities for NO oxidation achieved by different amounts of CeO2-modified Pt/SiO2-Al2O3 catalysts Pt/SiO2-Al2O3-wCeO2 (the mass fraction w being 0%, 5%, 10%, 15%, 30%), prepared using step-wise impregnation, were investigated in the presence and absence of CO and C3H6. The results showed that the NO oxidation activity could be efficiently improved by modification of CeO2, No.6 HUANG Yu-Fen et al.: Effects of CeO 2 Addition on Improved NO Oxidation Activities of Pt/SiO 2-Al 2 O 3 DOCs 1243 wherei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…7 The peak II located at 174 °C was ascribed to the reduction of Pt oxides weakly interacting with alumina surface. 15 Besides, the peak III at 270 °C belonged to the reduction of bulk PtO x such as PtO and PtO 2 species. 7 For Pt/CeSA and Pt/CeO 2 catalysts, the area of all reduction peaks was larger than that of Pt/SA, indicating that not only Pt oxides but also the surface oxygen of ceria were reduced.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 89%
See 4 more Smart Citations
“…7 The peak II located at 174 °C was ascribed to the reduction of Pt oxides weakly interacting with alumina surface. 15 Besides, the peak III at 270 °C belonged to the reduction of bulk PtO x such as PtO and PtO 2 species. 7 For Pt/CeSA and Pt/CeO 2 catalysts, the area of all reduction peaks was larger than that of Pt/SA, indicating that not only Pt oxides but also the surface oxygen of ceria were reduced.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 89%
“…This result was consistent with TEM measurement in our previous work, which showed that the mean sizes of Pt particles in Pt/SA and Pt/15CeSA catalysts were 26.5 and 6.3 nm, respectively. 15 However, no diffraction peaks of Pt were observed in XRD patterns for Pt/ CeO 2 , demonstrating that the dispersion of Pt over Pt/CeO 2 was higher than that over Pt/15CeSA. Nevertheless, shown by the results of the activity test, the catalytic performance of Pt/ CeO 2 was greatly lower than that of Pt/15CeSA, because the catalytic activity of the catalyst was simultaneously influenced by multifarious factors.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 92%
See 3 more Smart Citations